The Development of Comic Learning Media Assisted by Canva Application on Science Subject for 4th Grade Elementary School Students - Putri, Dhara Atika; Sukron, Muhammad; Putri, Elsa Gustyananda (TOFEDU: The Future of Education Journal, 2025)
This research is motivated by the limited use of engaging and enjoyable learning media, particularly in the Science (IPAS) subject. The lack of visual aids such as images or illustrations makes learning less stimulating for students and impacts their understanding of the material. Therefore, there is a need for innovative and creative learning media, one of which is the creation of comics as a tool to enhance students' learning outcomes. This research is a type of research and development (R&D). The development model used is the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The trial was conducted with 4th-grade students at SD Negeri 01 Padang Laweh, using data collection techniques such as validity, practicality, and effectiveness tests. The validation results for the comic learning media showed a content (material and language) validation score of 96.42%, categorized as very valid, and a teaching module validation score of 84.37%, categorized as very valid. The practicality test conducted by educators and 4th-grade students resulted in a score of 93.97%, categorized as very practical. The effectiveness test, based on learning outcome tests from the 4th-grade students, obtained a score of 82.54%, categorized as very effective.